RETRACTED: Uncovering water quality and evaluating vulnerabilities of small-scale fisheries in Chilika Lagoon, India - Nair, Navya Vikraman; Nayak, Prateep Kumar (Frontiers in Marine Science, 2023)
Small-scale fisheries (SSFs) play a strong role in sustaining millions of livelihoods, food security, nutrition, and income globally but the fishers engaged in this sector simultaneously experience high levels of vulnerability and processes of marginalisation. Several factors are attributed to the multidimensional vulnerabilities the small-scale fishers experience, spanning both natural (e.g., natural disasters, ecosystem change) and anthropogenic (e.g., policy change, hydrological interventions, aquaculture) pressures. While there is much literature on various natural and human drivers of vulnerability in small-scale fishery communities, an absence of research connecting vulnerability with water quality is evident. Fisher communities often talk about fish in relation to the health of their aquatic habitats wherein water quality is seen as a key parameter. The link between healthy fish and good quality water has significant implications for strong and viable fishing communities. This paper examines these links further by focusing on the nature of vulnerabilities caused by water quality changes in the small-scale fishery system of Chilika Lagoon in India. We undertake detailed analysis of the invasive shrimp aquaculture activities and hydrological interventions for opening of a lagoon inlet with the Bay of Bengal as two dominant drivers adversely impacting water quality and increasing vulnerabilities of the entire small-scale fisheries social-ecological system. Our analysis suggests that there are strong interconnections between changes in water quality and the levels of vulnerabilities in the SSFs of Chilika Lagoon. Pollutants such as pesticides, and organic compounds accumulate in fish tissues and affect their growth, reproduction, and overall health. This led to declines in fish populations, making it more difficult for fishers to make a living. In addition to direct impacts on fish populations, poor water quality also has indirect effects on the social and economic vulnerability of SSFs. For example, contamination of water sources led to the reduced number of fish species reducing the amount of time fishers can spend on fishing activities. This also affected the marketability of fish products, reduced income and increased poverty. To fully understand the interconnections between water quality and vulnerability in SSFs in Chilika Lagoon, it is important to consider both environmental and social factors, as well as the complex feedback loops between these factors. The study helps in bridging a crucial gap in our understanding of the role of water quality in vulnerability analysis within resource dependent communities. We conclude with key insights on possible coping responses and adaptive capacity necessary for the small-scale fisheries communities to transition toward viability.